Physicochemical properties and process contaminants analysis of flaky egg-free rolls incorporated with buckwheat (Fagopyrum esculentum Moench) - Yung-Jia Chan; Yu-Tsung Cheng; Wen-Chien Lu; Po-Hsien Li (CyTA - Journal of Food, 2023)
ABSTRACTThe fortification of buckwheat (Fagopyrum esculentum Moench) with rheological characteristics, nutritional properties, and formation of contaminants in wheat flour-based flaky rolls was studied. Higher content of buckwheat flour increased the antioxidant capacity, and phenolic, protein, fiber, rutin, and quercetin contents, leading to the development of a nutritionally improved product. The contents of the process contaminants, for example, the acrylamide, hydroxymethylfurfural (HMF), and furfural ranged from 147.25–262.19 μg/kg, 19.17–73.56 mg/kg, and 1.34–4.55 mg/kg, respectively, when buckwheat was added in the range of 0–30%. Parallelly, the production levels of methylglyoxal (MGO) and glyoxal (GO) were 4.09–23.55 and 0.69–2.05 mg/kg in the buckwheat substitution range of 0–30%. Shortly, even though incorporating 10% buckwheat flour had the best sensory scores, 20% was the most suitable substitution rate in terms of controlling the contaminants produced during processing while enhancing the nutritional properties of flaky rolls.